PENDAMPINGAN SUAMI TERHADAP KELANCARAN PROSES PERSALINAN DI BPM ARIFIN S SURABAYA - Irmah Nur Lailia; Fauziyatun Nisa (Jurnal Ilmiah Kesehatan, 2014)
The continuity of laboring process can be seen from the length of delivery takes and do not undergo complications during childbirth. In fact, there are many women who have suffered due to an excessive fearness therefore they had labor disfluencies which can be hindering the delivery process of laboring. This study aims to determine the relationship between mentoring husband with the continuity of labor process in BPM Arifin S Surabaya.The design which is used is analytic cross-sectional study design. The population study is all women who is giving birth in the moment of January to May with 142 respondents. The sampling technique using simple random sampling, 61 respondents. The independent variable (mentoring husband) with the dependent variable (continuity laboring process). The collecting data using partograf. Data anlysis using Chi-Square α = 0.05.The results showed that 85.3%of respondents who accompanied by husband during laboring process, they will have precious continuity of laboring. The results of chi-square test with α = 0.05 is ρ = 0.000 obtained significant ρ < α Ho have been ignored, it means that there is a relation between accompanied husband and the continuity laboring process.The concusions of this study, there is a relation between accompanying by husband while laboring process and a fluency of laboring process. Unaccompanied by husband while labor process will increase the risk uncontinuity of laboring process. Hence, this is truly necessary for husband having counseling about the importance of accompanying mothers while laboring process.